Development of the axial skeleton during the early ontogeny of pimelodus sp. (pisces: pimelodidae) (2010)
ABSTRACT: The knowledge on the somatic development during the early life stage of Colombian fish is scarce. Some meristic characteristics such as vertebrae and myomere number are considered good tools in the taxonomic identification of fish species. However, little is known on the development of these structures, their limits during the larval stages of development, and its conservation during the adult stage. The genus Pimelodus is distributed in South America and has commercial importance as a food resource for riverside human communities. Its species P. groskopffi and P. blochii reproduce with floods and its densities are the highest in ichthyoplankton conformation in the Magdalena River. By means of coloration and transparentation techniques recommended in bone and muscle studies in larvae, myomere and vertebrae quantification in three zones of the spinal cord (cephalic, pre-anal and post anal) and their relation to the three development phases in Pimelodus sp. Larvae are presented.